2004
DOI: 10.1136/ard.2003.012724
|View full text |Cite
|
Sign up to set email alerts
|

Trends in hip and knee joint replacement: socioeconomic inequalities and projections of need

Abstract: Objectives: To examine trends in primary and revision joint (hip and knee) replacement in England between 1991 and 2000. Methods: Analysis of hospital episodes statistics between 1 April 1991 and 30 March 2001 for total hip replacement (THR) and total knee replacement (TKR). Descriptive statistics and regression modelling were used to summarise patients' demographic and clinical characteristics and to explore variations in joint surgery rates by age, sex, and deprivation. Results: Between 1991 and 2000, the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

18
197
3
9

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 299 publications
(227 citation statements)
references
References 20 publications
18
197
3
9
Order By: Relevance
“…Their willingness to undergo surgery however is equal to their more educated peers; therefore, patient willingness does not account for the treatment discrepancy [11]. The disparity between patients with OA with low socioeconomic status and access to total joint surgery exists even in countries with equal access to health care [5,6,11]. Although these individuals are at risk for lower patient-reported outcomes than more educated patients, they still have marked improvements and benefit from the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Their willingness to undergo surgery however is equal to their more educated peers; therefore, patient willingness does not account for the treatment discrepancy [11]. The disparity between patients with OA with low socioeconomic status and access to total joint surgery exists even in countries with equal access to health care [5,6,11]. Although these individuals are at risk for lower patient-reported outcomes than more educated patients, they still have marked improvements and benefit from the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Currently 5% of all TKAs are performed in patients 85 years or older [3,19], but with large expansions in this population group expected [10], it is probable the elderly will account for a greater proportion of cases in future years. Furthermore, with increased awareness of TKA, it can be expected demand will increase [9,15]. Although TKA reduces pain and improves function in general populations of patients with joint disease [21], such postoperative outcomes as these in the octogenarian population are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research from the United Kingdom showed that individuals who received means-tested welfare benefits were less likely to have knee arthritis managed by a hospital consultant and were less likely to be on a waiting list for knee replacement, compared with individuals who were not receiving benefits (10). Further research has also reported lower rates of hip and knee replacement in the United Kingdom for persons with the lowest socioeconomic background (11). A similar disparity in surgery rates also exists in the United States, with differences in health beliefs, economic, and personal resources cited as possible causes (12).…”
Section: Introductionmentioning
confidence: 99%
“…Potential contributing factors may include increased difficulty obtaining health care information, lower health literacy, or reduced access to health professional services. Studies conducted in the United States and the United Kingdom found that patients with the lowest socioeconomic status had significantly lower rates of joint replacement, but explanations for these findings have been limited (11,26). An increased aversion to undergo surgery is unlikely to be responsible, because a Canadian study reported that patients from lower socioeconomic backgrounds were equally willing to undergo joint replacement when compared with those of higher socioeconomic status (27).…”
mentioning
confidence: 99%